First detected Helicobacter pylori infection in infancy modifies the association between diarrheal disease and childhood growth in Peru - Windle, Henry; Kelleher, Dermot (My University, 2014)
BACKGROUND: In endemic settings, Helicobacter pylori infection can occur shortly after birth and may be associated with a reduction in childhood growth. MATERIALS AND METHODS: This study investigated what factors promote earlier age of first H. pylori infection and evaluated the role of H. pylori infection in infancy (6-11 months) versus early childhood (12-23 months) on height. We included 183 children near birth from a peri-urban shanty town outside of Lima, Peru. Field-workers collected data on socioeconomic status (SES), daily diarrheal and breast-feeding history, antibiotic use, anthropometrics, and H. pylori status via carbon 13-labeled urea breath test up to 24 months after birth. We used a proportional hazards model to assess risk factors for earlier age at first detected infection and linear mixed-effects models to evaluate the association of first detected H. pylori infection during infancy on attained height. RESULTS: One hundred and forty (77%) were infected before 12 months of age. Lower SES was associated with earlier age at first detected H. pylori infection (low vs middle-to-high SES Hazard ratio (HR) 1.59, 95% CI 1.16, 2.19; p = .004), and greater exclusive breast-feeding was associated with reduced likelihood (HR 0.63, 95% CI 0.40, 0.98, p = .04). H. pylori infection in infancy was not independently associated with growth deficits (p = .58). However, children who had their first detected H. pylori infection in infancy (6-11 months) versus early childhood (12-23 months) and who had an average number of diarrhea episodes per year (3.4) were significantly shorter at 24 months (-0.37 cm, 95% CI, -0.60, -0.15 cm; p = .001). DISCUSSION: Lower SES was associated with a higher risk of first detected H. pylori infection during infancy, which in turn augmented the adverse association of diarrheal disease on linear growth.
PUBLISHED
doi: 10.1111/hel.12130
Keywords: Helicobacter pylori; Cancer; Immunology, Inflammation & Infection; International Development